Best Practice Inovasi Pelayanan Publik “Laboratorium Kemiskinan” Di Kabupaten Pekalongan - Kurniani Wismaningsih; Retno Sunu Astuti; Ida Hayu Dwimawanti; Budi Puspo; Teuku Afrizal (Universitas Negeri Medan, 2021)
This study aims to examine the best practice of public service innovation